The Use Of Macromedia Flash Player As Media To Improve Students’ Reading Skill - Syaifudin Latif Darmawan; Okta Widia Sari (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
Abstract The study is classroom action research. It is conducted at Junior High School of PGRI 4 Labuan Ratu.The subject of the research is eight students of Junior High School of PGRI 4 Labuan Ratu. The objectives of the research are: 1) to know how macromedia flash player can improve students’ reading skill at eight year of Junior High School of PGRI 4 Labuan Ratu; 2) to know how is the classroom situation when macromedia flash used in teaching reading at eight year of Junior High School of PGRI 4 Labuan Ratu. The research is conducted in two cycles. The procedure of the research consists of identifying the problem, planning the action, implementing the action, observing the action, and reflecting the result of the research. To colect the data, the writers employ observation, interview and test. In the meantime, to analize the data, the writers make use of some steps: (1) Data Reduction (2) Data Display (3) Data Conclusion. The result of the research indicates that there is an improvement on students’ reading skill; (1) the students are able to identify the specific information of the text; (2) the students are able to identify the purpose of the text; (3) the students are able to identify the generic structure of the text. The students’ scores are as follow: The average of pre test is 51,46%. The average of post test 1 is 69,59% and the average of post test 2 is 82,34%. Therefore, it can be concluded that, teaching reading using macromedia flash player is quiet effective for the eight year students of Junior High School of PGRI 4 Labuan Ratu.